The Relationship of Mother's Age, Parity, and Abnormalities in Fetal Location with The Incidence of Premature Ruptur of Membranes in The Regional Public Hospital of North Lombok - Safa, D. Jilan Haura; Shammakh, Adib Ahmad; Karmila, Dany; Setyobudi, Irwan (Jurnal Biologi Tropis, 2024)
Premature rupture of membranes (PROM) is one of the main causes of the high newborn mortality rates and maternal mortality rate (MMR), which continue to be significant global health challenges. The purpose of this study is to examine the association between the occurrence of PROM at the North Lombok Regional Public Hospital and maternal age, parity, and fetal anomalies. This research uses a case-control study design and is an analytical observational study. Purposive sampling was utilized to choose the research sample, which included 186 people in total. The chi-square test was used to analyze the data and determine how the variables related to one another. According to the study's findings, 120 (64.5%) respondents were not at risk, while 66 (35.5%) were. Of the respondents, 131 (70.4%) had parity without risk, while 55 (29.5%) had parity at risk. Respondents with fetal abnormalities were 28 (15.1%) and 158 (84.9%) had normal fetuses. Age and the frequency of premature membrane rupture are related; the p-value is 0.022 and the OR is 2.145. With a p-value of 0.024 and an OR of 2,203, there is a correlation between parity and the frequency of premature membrane rupture. Premature rupture of the membranes and fetal abnormalities do not correlate, as indicated by the p-value of 0.538. The incidence of PROM is correlated with maternal age and parity, although there is no significant link between PROM and fetal abnormalities.